A paleoclimate rainfall reconstruction in the Murray‐Darling Basin (MDB), Australia: 2. Assessing hydroclimatic risk using paleoclimate records of wet and dry epochs. Issue 10 (23rd October 2015) - Ho, Michelle; Kiem, Anthony S.; Verdon‐Kidd, Danielle C.
Abstract: Estimates of hydrological risk are crucial to enable adequate planning and preparation for extreme events. However, the accurate estimation of hydrological risk is hampered by relatively short instrumental records in many parts of the world. Information derived from climate‐sensitive paleoclimate proxies provide an opportunity to resolve hydroclimatic variability, but many regions, such as Australia's Murray‐Darling Basin (MDB), currently lack the suitable in situ proxies necessary to do this. Here new MDB rainfall reconstructions are presented based on a novel method using paleoclimate rainfall proxies in the Australasian region spanning from 749 B.C.E. to 1980 C.E. Our results emphasize the need to develop additional reconstructions and, with the companion paper, demonstrate how this information can be used to benefit water resource management. This study shows that prior to the twentieth century, both dry and wet epochs have persisted for longer periods than observed in the instrumental record—with the probability of both dry and wet periods exceeding a decade at least 10 times more likely prior to 1883 than suggested by the instrumental records. Some reconstructed rainfalls exceeded the instrumental range (i.e., drier dry epochs and wetter wet spells) despite a systematic underestimation of extremes due to a combination of proxy quality and model bias. Importantly, the results demonstrate that the instrumental record does not cover the full range of hydroclimatic variability possible in the MDB. Therefore, hydroclimatic risk assessments based on the instrumental record likely underestimate, or at least misinterpret, the frequency, duration, and magnitude of wet and dry epochs. Key Points: Drought and flood risks are underestimated if pre‐1900 information is not used Evidence of longer wet and dry epochs prior to twentieth century Evidence of more frequent wet and dry epochs prior to twentieth century